Bioarchaeological Research of The Home Army’s Soldiers From Raubiszki and Druzhyle Battles - Kadikinaitė, Jovita (Vilnius University Open Series, 2024)
This article covers the topic of Armia Krajowa’s soldiers and their manner-of-death. AK is a Polish underground military organization that was active during World War II and the post-war period until 1945. Since Vilnius region was occupied by Poland during the inter-war period (1920–1939), multiple historical events in which AK soldiers were fighting against German Nazis and Soviets took place in modern-day Lithuanian territories. Thus, a considerable number of single and mass burials of Polish partisans are uncovered in Lithuania. This research aims to reconstruct the manner-of-death of 9 AK partisans’ skeletal remains from two battles with the Soviets: Družiliai and Raubiškės. The results indicated a wide range of perimortal lesions sustained on the battlefield: perimortal fractures and gunshot wounds. The analysis also revealed pathological lesions that illustrated challenges individuals had faced in their daily partisanship – hard physical labor, malnutrition, non-specific stress.